Extracellular freezing induces a permeability transition in the inner membrane of muscle mitochondria of freeze-sensitive but not freeze-tolerant Chymomyza costata larvae - Štětina, Tomáš; Koštál, Vladimír (Frontiers in Physiology, 2024)
Background: Many insect species have evolved the ability to survive extracellular freezing. The search for the underlying principles of their natural freeze tolerance remains hampered by our poor understanding of the mechanistic nature of freezing damage itself. Objectives: Here, in search of potential primary cellular targets of freezing damage, we compared mitochondrial responses (changes in morphology and physical integrity, respiratory chain protein functionality, and mitochondrial inner membrane (IMM) permeability) in freeze-sensitive vs. freeze-tolerant phenotypes of the larvae of the drosophilid fly, Chymomyza costata. Methods: Larvae were exposed to freezing stress at −30°C for 1 h, which is invariably lethal for the freeze-sensitive phenotype but readily survived by the freeze-tolerant phenotype. Immediately after melting, the metabolic activity of muscle cells was assessed by the Alamar Blue assay, the morphology of muscle mitochondria was examined by transmission electron microscopy, and the functionality of the oxidative phosphorylation system was measured by Oxygraph-2K microrespirometry. Results: The muscle mitochondria of freeze-tolerant phenotype larvae remained morphologically and functionally intact after freezing stress. In contrast, most mitochondria of the freeze-sensitive phenotype were swollen, their matrix was diluted and enlarged in volume, and the structure of the IMM cristae was lost. Despite this morphological damage, the electron transfer chain proteins remained partially functional in lethally frozen larvae, still exhibiting strong responses to specific respiratory substrates and transferring electrons to oxygen. However, the coupling of electron transfer to ATP synthesis was severely impaired. Based on these results, we formulated a hypothesis linking the observed mitochondrial swelling to a sudden loss of barrier function of the IMM.